The Correlation Between Waist Circumference and Blood Pressure for People Aged 25 to 60 Years Old in Palur Village Ca III - Kurniawan, Adhy (Physiotherapy and Physical Rehabilitation Journal, 2022)
The digitalization era significantly influences human life, such as lifestyle and physical activity. Human life change happens because of the ease of access provided by digitalization to purchase goods from home. This matter becomes the predictor of waist circumference and body mass index increase with obesity risks. Larger waist circumference influences the increased intra-abdominal fat accumulation. This fat accumulation leads to obesity and hypertension. This research aims to determine the correlation between waist circumference and blood pressure of people aged from 25 to 60 years old in Palur village, CA III. This cross-sectional research used chi square data analysis. The results showed that 51 people out of 100 had a larger waist circumference than 90cm suffering from hypertension.